New bioactive mono-acyl glycerol ester from the Red Sea marine coral Sclerophytum levi - Basma H. Farouk; Asmaa M. Abdel-Tawab; Mohamed E. Mostafa; Fawzia Z. El-Ablack; El Sayed A. E. Hamed; Seif-Eldin N. Ayyad (Natural Product Research, 2026)

Geological mapping of Neoproterozoic rocks in Zug El-Bohar area, NW Red Sea rift system, Egypt: an integrated hyperspectral remote sensing, petrographic, and geochemical approach - Farouk Sayed; Aya S. Shereif; Ali Shebl; Árpád Csámer; Abdelhalim S. Mahmoud (Remote Sensing Applications: Society and Environment, 2026)

Structurally-controlled radioactive and rare metal mineralizations associated with potassic alteration in Umm Ara granitoids, southern Eastern Desert, Egypt: Implications from remote sensing, whole-rock chemistry, and geophysical data - Adel Fathy; Mokhles K. Azer; Abdelhalim S. Mahmoud; Farouk Sayed; Ahmed A. Masoud; Faris A. Abanumay (Journal of Geochemical Exploration, 2026)

Targeting metabolic dysfunction-associated steatotic liver disease with phytosomal silymarin and piperine: A natural alternative to fenofibrate in a rat model - Magdy Fouad Tawfik; Yasmin Sayed Hussein; Amany Helmy Hasanin; Walaa Baher; Nashwa El-Khazragy; Farouk Guindi Moawad; Mawada Abou El-Khair; Salwa M. El-Sayed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is an increasing global health concern with limited effective therapies. Silymarin exhibits hepatoprotective properties, but its utility is limited by poor bioavailability. This study evaluated a novel phytosomal silymarin formulation co-administered with piperine and lecithin, compared to fenofibrate, in an oxytetracycline-induced MASLD rat model. Twenty-five male Wistar rats were allocated into five groups: healthy control, MASLD control, fenofibrate (100 mg/kg), silymarin (500 mg/kg), or silymarin–piperine–lecithin phytocomplex (500/100/3 mg/kg) for 90 days. Parameters evaluated included serum liver enzymes, lipid profiles, hepatic histology, and hepatic PPAR-α expression. The phytocomplex formulation significantly reduced serum ALT, AST, ALP, and GGT, improved lipid profiles, and restored hepatic architecture, with MASLD-AS and PPAR-α expression demonstrating a marked reduction in hepatic injury and oxidative stress. The phytocomplex outperformed both fenofibrate and silymarin alone, likely due to enhanced bioavailability and synergistic antioxidant action comparable to fenofibrate treatment. This study demonstrates the potential of a phytosomal silymarin–piperine–lecithin complex as a natural therapeutic avenue for MASLD, outperforming a conventional lipid-lowering agent in this animal model. Future clinical and pharmacokinetic studies are warranted.

Paleoenvironmental setting and facies analysis of the Middle Miocene carbonate platform in north Western Desert, Egypt - Ibrahim M. Ied; Sherif Farouk; Sayed Abd El-Azeam; Mohammad Abd-Elazez; Ibtsam A. Abd EL-Rauf (Carbonates and Evaporites, 2025)
The Marmarica Formation in the north Western Desert (NWD) of Egypt is predominantly composed of Middle Miocene carbonate rocks. A detailed microfacies and paleoenvironmental analysis was conducted on six representative surface sections extending from the Siwa to Matruh areas: Dakrur, North Siwa (NS), Siwa-Matruh 1 (SM1), Siwa-Matruh 2 (SM2), Abu Khrait, and Agiba. Field observations and lithological data indicate that the Marmarica Formation can be subdivided into three informal members: lower, middle, and upper. A distinct facies shift is observed from interbedded shale and carbonate in the Siwa area to predominantly carbonate facies towards the north in the Siwa-Matruh and Matruh areas. Microfacies analysis of the studied sections identified twelve distinct microfacies types, which are grouped into three main facies associations, corresponding to three paleoenvironmental settings: restricted lagoonal platform interior, open marine shelf (platform top), and high-energy platform shoal. Based on the vertical and lateral distribution of these facies, a homoclinal ramp depositional model is proposed, revealing a clear deepening trend from south to north. In the southern Siwa area, the depositional system evolves vertically from a protected, restricted lagoon to open shelf and shoal settings. Towards the north, the environment becomes progressively deeper, dominated by fluctuations between open marine shelf and high-energy shoal environments. Sequence stratigraphic analysis identified three third-order transgressive-regressive (T-R) depositional sequences (SQ1, SQ2, SQ3), each comprising transgressive system tracts (TST) and highstand system tracts (HST) and are separated by two sequence boundaries (SB1 and SB2). These sequences correspond to global eustatic cycles—such as Haq et al. 1987 and Hardenbol et al. 1998- and correlate with equivalent Miocene carbonate systems in the Tethyan realm highlighting the interplay of eustatic sea-level changes and regional tectonics on carbonate platform evolution during the Langhian–Serravallian stages.

Dietary supplementation of ewes with Astragalus membranaceus root extract enhanced the feto-maternal hemodynamics, fetoplacental development, and lambs’ growth rate - Hossam R. El-Sherbiny; Fady Sayed Youssef; Mohammed Hamed Eldawy; Ismail Abdelraouf Elnady; Emad Mohammed Elken; Mohammed Hamdy Farouk; Ahmed Ezzat Ahmed; Maha Abdullah Momenah; Ramya Ahmad Sindi; Seham Samir Soliman; Haney Samir (Small Ruminant Research, 2025)

Whole genome sequencing identifies monogenic disease in 56.1% of families with early-onset steroid-resistant nephrotic syndrome - Neveen A. Soliman; Mohamed A. Elmonem; Ahmed F. El-Sayed; Eman Ramadan; Ahmed M. Badr; Fatma M. Atia; Rasha Helmy; May O. Amer; Ahmed Abd El-Raouf; Fadya M. El-Garhy; Omnia M. Abdel-Haseb; Tokka M. Hassan; et al. (Human Genetics, 2025)
Genetic causes of steroid-resistant-nephrotic-syndrome (SRNS) represent a rapidly growing number of monogenic diseases. The reported diagnostic yield of various studies applying genetic panels and exome-sequencing to diagnose SRNS is usually < 30%. We performed genome-sequencing in a cohort of Egyptian SRNS patients. We recruited 47 SRNS patients belonging to 41 unrelated families [28 males/19 females; median (range): 6 (0.5–22 years)]. We established a pipeline for genome sequencing, bioinformatics analysis, variant curation and protein modeling at the Egypt Center for Research and Regenerative Medicine (ECRRM). Disease-causing variants were detected in 27/47 patients (57.4%) belonging to 23/41 families (56.1%), including nine novel variants in NPHS1, NPHS2, COL4A3, MYO1E, NUP93, PLCE1, PODXL, SMARCAL1 and WT1 . Novel variants were confirmed by Sanger sequencing and were segregated in families of affected patients. NPHS2 was the most common causative gene in 8/23 (34.8%) of confirmed families, followed by NPHS1 , WT1 , and SMARCAL1 in 2/23 families (8.7%) each. All detected missense variants were evaluated through protein modeling and were predicted deleterious. Our study expanded the spectrum of SRNS disease-causing variants and revealed a monogenic cause in 56.1% of investigated families. In our cohort, no deep intronic or regulatory variants were detected by genome-sequencing. Pursuing genetic diagnosis in SRNS patients is crucial to inform clinical decision making, genetic counseling, transplantation strategy and prenatal diagnosis thus improving clinical outcome of affected patients.

Molecular typing of Protoparvovirus carnivoran 1 in Egyptian cats diagnosed with feline panleukopenia - Mahmoud S. Safwat; Samah El-Sayed M.; Mohamed E. Ali; Omar S. Saeed; Haitham M. Amer; Othman N.O. Mansour; Ayah M. Hassan; Manar M. Farouk (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Green hybrid coagulants for water treatment: An innovative approach using alum and bentonite clay combined with eco-friendly plant materials for batch and column adsorption - Sidra Saqib; Amna Muneer; Ruba Munir; Murtaza Sayed; Muhammad Waqas; Tayyiba Aliyam; Fazila Younas; Mohammad Abul Farah; Mohamed Farouk Elsadek; Saima Noreen (Environmental Research, 2024)

Structural architecture and tectonic evolution of the Shabrawet Syrian Arc inverted zone at the Northern termination of the Gulf of Suez rift, Egypt - Mohamed S. Hammed; Farouk Sayed; Ahmed G. Shided; Ahmed W. Hussein (International Geology Review, 2022)

A critical study of interactive fluoride adsorption by raw marine organisms and a synthetic organic 2-amino-3-cyano-4(4-nitrophenyl)-6-phenylpyridine as adsorbent tools - Ghada Farouk El-Said; El-Sayed M. Abdelrehim; Mohamed El-Sayed Elba; Sara M. H. Abdel Kawy (Environmental Monitoring and Assessment, 2019)

Pharmacological evaluation of some novel synthesized compounds derived from spiro(cyclohexane-1,2′-thiazolidines) - Eman M. Flefel; Hayam H. Sayed; Ahmed I. Hashem; Emad A. Shalaby; Walaa El-Sofany; Farouk M. E. Abdel-Megeid (Medicinal Chemistry Research, 2014)